On Quasi-Sasakian Manifolds - Sazak, Ahmet; Yıldız, Ahmet (My University, 2019)
In this paper we study three-dimensional quasi-Sasakian manifolds admitting the Schoutenvan Kampen connection. Also, we study D-homothetic deformations on three-dimensional quasi-Sasakian manifolds admitting Schouten-van connection and projectively flat threedimensional quasi-Sasakian manifolds admitting scv connection.